Bioactive glasses as carriers for bioactive molecules and therapeutic drugs: a review - Hum, Jasmin; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2012)
Bioactive glasses (BG) show great promise for bone tissue engineering based on their key properties, e.g., biocompatibility, biodegradability, osteoconductivity as well as osteogenic and angiogenic potential, which make them excellent candidates for bone tissue scaffolds and bone substitute materials. Recent work has shown that dissolution products of bioactive glasses have the potential to induce angiogenesis in addition to their known effect of influencing gene expression and promoting osteoblastic differentiation. One of the most interesting features of BG is their ability to bond both to soft and hard tissues, depending on their composition. To intensify the positive impact of BG for medical applications, there are considerable research efforts on using bioactive glass based platforms as carriers for the encapsulation, delivery and controlled release of bioactive molecules and therapeutic drugs. Different types of bioactive glasses have been considered in combination with different therapeutic drugs, hormones, growth factors and peptides. Using bioactive glasses as drug delivery system combines thus the effectiveness of therapeutic drugs (or bioactive/signaling molecules) with the intrinsic advantages of this inorganic biomaterial. Considering research carried out in the last 15 years, this review presents the different chemical compositions and morphologies of bioactive glasses used as carrier for bioactive molecules and therapeutic drugs and discusses the expanding potential of BG with drug delivery capability focusing in the field of bone tissue engineering. © Springer Science+Business Media, LLC 2012.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.bioact